Impact of an oral care subsidization reform on intersectional inequities in self-rated oral health in Sweden - Cynthia Anticona; Anna Liisa Suominen; Pernilla Lif Holgerson; Per E Gustafsson (BMC, 2024)
Abstract Background Oral health in Sweden is good at the population level, but seemingly with persisting or increasing inequities over the last decades. In 2008, a major Swedish reform introduced universal partial subsidies to promote preventive care and reduce the treatment cost for patients with extensive care needs. This study aimed to apply an intersectional approach to assess the impact of the 2008 subsidization reform on inequities in self-rated oral health among adults in Sweden over the period 2004-2018. Methods Data from 14 national surveys conducted over 2004-2018 were divided into three study periods: pre-reform (2004-2007), early post-reform (2008-2012) and late post-reform (2013-2018). The final study population was 118,650 individuals aged 24-84 years. Inequities in self-rated oral health were examined by intersectional analysis of individual heterogeneity and discriminatory accuracy across 48 intersectional strata defined by gender, age, educational level, income, and immigrant status. Results Overall, the prevalence of poor self-rated oral health decreased gradually after the reform. Gender-, education- and income-related inequities increased after the reform, but no discernible change was seen for age- or immigration-related inequities. The majority of intersectional strata experienced patterns of persistently or delayed increased inequities following the reform. Conclusions Increased inequities in self-rated oral health were found in most intersectional strata following the reform, despite the seemingly positive oral health trends at the population level. Applying an intersectional approach might be particularly relevant for welfare states with overall good oral health outcomes but unsuccessful efforts to reduce inequities.